THE INFLUENCE OF SMOKING BEHAVIOR ON SOCIAL JETLAG, CHANGES IN BODY MASS INDEX, AND MENTAL HEALTH IN STUDENTS DURING AND AFTER THE COVID-19 PANDEMIC (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Introduction: Smoking is a major public health problem globally and nationally in Indonesia. Smoking is a risk factor for various non-communicable diseases such as cancer, cardiovascular and other degenerative diseases. Social jetlag is a circadian rhythm phenomenon that has surfaced in the recent electricity era where social jetlag is a measure of accumulated daily sleep deficits. The impact of jetlag has a bad influence on health and is associated with bad health behavior. Obesity has recently become a global phenomenon, apart from being a risk for various non-communicable diseases, during the COVID-19 pandemic obesity was a determinant of the poor clinical condition of a person who was attacked by the COVID-19 virus. Mental health is also starting to emerge and become a phenomenon that is often found in late adolescents. The transition period of the learning system from online to offline is a phase that demands adaptability for students. Does smoking behavior in this group who experience changes from online to offline learning systems affect social jetlag, changes in body mass index, and mental health. Purpose: evaluate the effect of smoking on social jetlag, changes in body mass index and mental health in adolescents in the transition era of online to offline learning. Methods: a cross-sectional design study evaluating differences in average social jetlag, changes in body mass index, and levels of depression, anxiety and stress (Indonesian version of the DASS-21) between smoking and non- smoker students. Data from respondents were obtained by filling in a Google form which was distributed through social media networks with WhatsApp, Instagram, Facebook and Line platforms. Results: as many as 389 students voluntarily participated in this study. Student smokers have significantly higher body mass index during the pandemic, and lower BMI when offline. Social jetlag, levels of depression, anxiety and stress are increasing. Conclusion: Smoking increases the risk of social jetlag, significant changes in body mass index, and mental health disorders during the online-to-offline transition.
Keywords: smoking behavior, social jetlag; body mass index; mental health; the COVID-19 pandemic